Ethics and the Election of 1996 - Ballard, Steve (Maine Policy Review, 1996)
In the Margaret Chase Smith Essay, Steve Ballard discusses the Maine Code of Election Ethics: its origins, its successes and failures, and how it can be improved. Pioneered by the Margaret Chase Smith Library in Skowhegan, the code is a unique response to a national problem—making representative government work.